Accessible protocol for asymmetric hydroformylation of vinylarenes using formaldehyde. Issue 16 (18th March 2015) - Morimoto, Tsumoru; Fujii, Tetsuji; Miyoshi, Kota; Makado, Gouki; Tanimoto, Hiroki; Nishiyama, Yasuhiro; Kakiuchi, Kiyomi
Abstract : The rhodium(i )/chiral Ph-bpe-catalyzed reaction of vinylarenes with formaldehyde provides an accessible protocol for asymmetric hydroformylation to enantioenriched aldehydes in high yields. Abstract : We report herein on an accessible protocol for the asymmetric hydroformylation of vinylarenes using formaldehyde as a substitute for syngas. The regioselectivity (branched/linear = up to 96/4) and enantioselectivity (up to 95% ee) can be attributed to the use of chiral Ph-bpe as a ligand.